Profound Leadership and Adult Education: An integrative Review of the Literature - Heidi Scott; Davin J Carr-Chellman; Leslie Hammes (Adult Education Research Conference, 2019)
This integrative literature review presents profound leadership through the lens of key characteristics of servant leadership, authentic leadership, level five leadership, profound leadership, transformational leadership, and spiritual leadership.
Keywords: profound leadership; leadership theories